PENGARUH KODE ETIK APIP TERHADAP KINERJA AUDITOR PEMERINTAH PADA INSPEKTORAT PROVINSI MALUKU UTARA - Kneefel, Engelita O.; Sondakh, Jullie J.; Mawikere, Lidia (Universitas Sam Ratulangi, 2017)
This research aims to and analyze the effect of APIP Ethical Codes (Integrity, Objectivity, Privacy, and Capability) through the performance of auditor in Maluku Utara Provincial Inspectorate which used quantitative method, with the multiple regression models. The research population is 44 Auditors and sampel is 44 Auditors. Primary data obtained by quistionaire distribution throughout 44 respondents which all fullfiled and operable. Independent variable of this research is APIP Ethical Codes (Integrity, Objectivity, Privacy, and Capability), and dependent variable is government performance of auditor. Regards to the result, therefore variable that APIP Ethical Codes simultaneously affect the government performance of auditor and partial that variable Objectivity affect the government performance of auditor, whereas variable Integrity, Privacy, and Capability rejected government performance of auditor.Keywords : Integrity, Objectivity, Privacy, Capability, And Performance Of Auditor